INTERVIEW WITH PROF.DR. ALPARSLAN ACIKGENC: WORLDVIEW AND SCIENCE - Saribas, Hakan; Acikgenc, Alparslan (RESEARCH CENTER ISLAMIC ECONOMICS-IKAM, 2014)
Prof.Dr. Alparslan Acikgenc had spoken to the our journal editor on July 25, 2013 at Besiktas Campus of Yildiz Technical University in Istanbul. The impact of worldview on science has been discussed in the interview with Alparslan Acikgenc. It is argued that scientific activities can not be separated from scientists' worldviews and that observations are loaded with theories, which are themselves rooted in a worldview. The existance of Islamic economics and its further developments depend on Islamic epistemology.
Keywords: Business & Economics